Transmission of tuberculosis (Mycobacterium bovis) by possums : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Jackson, R. (Massey University, 1995)
Tuberculosis caused by Mycobacterium bovis was diagnosed in 59 of 632 possums (Trichosurus vulpecula) individually identified over a 52 month period, during a longitudinal study of the naturally occurring disease in possums at a 21 hectare bush pasture location on a farm at Castlepoint in the Wairarapa. The disease exhibited marked spatial and temporal clustering and was continuously present in the population for the whole period. The disease had a relatively long duration of up to 22 months and four distinct stages were demonstrated in cross-sectional studies. Among tuberculous possums, prevalences of up to 0.15 (±0.11) were recorded in the first stage prior to development of gross lesions. After dissemination started, the disease showed rapid generalisation to multiple sites by haematogenous and/or lymphatic spread to the next stage when gross lesions were evident, particularly in lung, axillary and inguinal lymphocentres. In the third stage, lesions were disseminated through almost all lung lobes, discharging fistulae were common and kidney, intestine and mammary gland were commonly affected by both gross and microscopic lesions. Behaviour and outward signs of health were unaffected prior to the terminally-ill stage, lasting for up to 2 months. In common with other marsupials studied to date and in contrast with most eutherians, there are no popliteal lymph nodes and efferent drainage from the inguinal lymphocentre passes directly to the deep axillary group of lymph nodes via an inguinoaxillary trunk. All subcutaneous lymph drainage passes through either the superficial cervical or the axillary lymphocentres before entering the venous system. Studies of survival of Mycobacterium bovis organisms in different natural habitats showed a relatively short period of survival of M. bovis outside hosts and support a conclusion that environmental contamination of pasture, particularly in summer months, may be relatively unimportant in the epidemiology of tuberculosis in cattle, deer and possums. The weight of evidence favours transmission of infection by the respiratory route and it would seem that transmission of tuberculosis between possums occurs through two major and one minor pathway. The first major pathway is pseudo-vertical transmission from mother to joey during the rearing process. The second major transmission mechanism is direct horizontal transmission among adult possums with available evidence suggesting that this takes place around the locality where a possum dens, probably during competition and threat/agonistic behaviour and during courting and mating activity. The third and probably least important pathway is indirect transmission among mature possums. None of three ELISA assays reliably detected possums infected with tuberculosis and poor test performance was exacerbated by inconsistency between results from serially collected samples from known tuberculous possums.
Keywords: Tuberculosis; Mycobacterium bovis; Trichosurus vulpecula; Possum; Tuberculosis in animals; Epidemiology; Brushtail possum